Community Relations in the Ottoman Balkans of the Suleymanic Age: The Case of Avlonya (1520–1568) - Mehmet Kerim; Furkan Mert Aktaş; Menderes Kurt (Religions)
This study examines the relations between an exiled Jewish diaspora and the surrounding Muslim communities in the significant Ottoman Balkan city of Avlonya between 1520 and 1568. Having been expelled from Spain (1492) and Portugal (1496), numerous Sephardic Jews settled in Avlonya in the early sixteenth century, integrating into Ottoman social structures and making notable contributions to both the economic and demographic landscape of the city. This study examines the extent of the Jewish community’s assimilation into Avlonya and Ottoman society in the immediate aftermath of its arrival, assessing its pathways to integration, their limitations, and the dynamics of coexistence and mutual trust. It posits that in a relatively short period, the integration of Avlonya’s Sephardic Jews into both the city and society proved to be a positive success from the perspective of the state and the community itself. Evidence in support of this assertion is found in an examination of the tahrir defters and sharia court records (the primary sources of data for this research). The depth of the findings and the variety of research questions posed mean that this study has employed a mixed-methods approach, allowing for both quantitative and qualitative evaluations.